Karakteristik Mutasi EGFR pada Pasien Kanker Paru Jenis Adenokarsinoma yang Diterapi dengan Tyrosien Kinase Inhibitor (TKI) di Rumah Sakit Paru Dr. H.A Rotinsulu Bandung - Puspita, Desi; Dwi Astuti, Vitri; Rina; Sampurno, Edi (Universitas Muhammadiyah Prof. Dr. Hamka (UHAMKA Press), 2022)
This descriptive study describes the proportion of Epidermal Growth Factor Receptor (EGFR) mutations in lung cancer Adenocarcinoma patients at Rumah Sakit Paru (RS Paru) Dr. H. A Rotinsulu Bandung in the range of 2018 to 2020. EGFR mutations were examined using RGQ thera screen technology Real